Quaternary Ammonium Compound Disinfectants Reduce Lupus-Associated Splenomegaly by Targeting Neutrophil Migration and T-Cell Fate - Abdelhamid, Leila; Cabana-Puig, Xavier; Mu, Qinghui; Moarefian, Maryam; Swartwout, Brianna; Eden, Kristin; Das, Prerna; Seguin, Ryan P.; Xu, Libin; Lowen, Sarah; Lavani, Mital; Hrubec, Terry C.; et al. (Frontiers in Immunology, 2020)
Hypersensitivity reactions and immune dysregulation have been reported with the use of quaternary ammonium compound disinfectants (QACs). We hypothesized that QAC exposure would exacerbate autoimmunity associated with systemic lupus erythematosus (lupus). Surprisingly, however, we found that compared to QAC-free mice, ambient exposure of lupus-prone mice to QACs led to smaller spleens with no change in circulating autoantibodies or the severity of glomerulonephritis. This suggests that QACs may have immunosuppressive effects on lupus. Using a microfluidic device, we showed that ambient exposure to QACs reduced directional migration of bone marrow-derived neutrophils toward an inflammatory chemoattractant ex vivo. Consistent with this, we found decreased infiltration of neutrophils into the spleen. While bone marrow-derived neutrophils appeared to exhibit a pro-inflammatory profile, upregulated expression of PD-L1 was observed on neutrophils that infiltrated the spleen, which in turn interacted with PD-1 on T cells and modulated their fate. Specifically, QAC exposure hindered activation of splenic T cells and increased apoptosis of effector T-cell populations. Collectively, these results suggest that ambient QAC exposure decreases lupus-associated splenomegaly likely through neutrophil-mediated toning of T-cell activation and/or apoptosis. However, our findings also indicate that even ambient exposure could alter immune cell phenotypes, functions, and their fate. Further investigations on how QACs affect immunity under steady-state conditions are warranted.